„Inklusive, chancengerechte Bildung durch die Kooperation von Lehrenden verbessern? – Fragen und Perspektiven im Rahmen des Aufbaus einer OER-Community für die Primarstufenlehrkräftebildung“. Workshopbeitrag im Rahmen der BMBF-Vernetzungstagung: OER im Blick. Fördern. Vernetzen. Fortentwickeln. Jena. - Büker, Petra; Oevel, Gudrun; Herding, Jana; Bruhnke, Lorena

Effect of Strain Rate on the Deformation Behavior and Energy Absorption Characteristics of LPBF-Processed Ti2448 Microarchitectured Lattice Structures - Ghosh, Koustav; Milaege, Dennis; Steinmeier, Paul; Schaper, Mirko; Hoyer, Kay-Peter; Pramanik, Sudipta (Journal of Materials Engineering and Performance)

Gendersensible Bildung als Querschnittsaufgabe im Lehramtsstudium - Decker, Claudia; Möhwald, Aiko Julia; Uppenkamp, Vera; Westphal, Petra (Beiträge zur Schulentwicklung)

Wenn Gemeinden sich selbst organisieren. Evaluationsstudie - Reis, Oliver; Hofmeister, Lisa; Weber, Carla (PGR ohne amtliches Mitglied. Welche Konsequenzen hat der Rückzug von Hauptamtlichkeit aus der PGR-Arbeit für die Selbstorganisation des Gremiums? Modellraum 2)

PGR ohne amtliches Mitglied

Bajo el signo de la abducción: la investigación de lo fantástico en la narrativa policial argentina desde 1950 hasta la actualidad - Schmitz, Sabine (Diálogos con lo fantástico en el policial latinoamericano)

ANALYZING STUDENTS’INFORMAL APPROACHES TO CREATING DECISION TREES IN THE CLASSROOM - Fleischer, Franz Yannik; Biehler, Rolf (Proceedings of the 48th Conference of the International Group for the Psychology of Mathematics Education: Research Reports, Vol. 1)

Guaranteed-Quality Rational Bézier Guarding - Khanteimouri, Payam; Campen, Marcel (Computer-Aided Design)

Welches Wissen nutzen Studierende bei der Planung von Physikunterricht mit digitalen Medien? - Jordans, Melanie; Riese, Josef (Entdecken, lehren und forschen im Schülerlabor. Gesellschaft für Didaktik der Chemie und Physik. Jahrestagung in Bochum 2024)

Diálogos con lo fantástico en el policial latinoamericano

Trauma-Spuren und gefährdete Existenzen. Zu zwei Erzählungen Que Du Luus - Morrien, Rita (Literatur in Westfalen. Beiträge zur Forschung 21)

Morning clock gene expression in young adults of early and late chronotypes - Krueger, Bettina; Rajcsanyi, Luisa Sophie; Hundertmark, Katharina; Stutz, Bianca; Hinney, Anke; Buyken, Anette E. (Scientific Reports)
Abstract Variations in circadian rhythm-related genes influence the individual chronotype. Here, we hypothesize that the peak of clock gene expression at 7 a.m. differs between young adults with a late chronotype and young adults with an early chronotype. Participants of the Chronotype and Nutrition nutritional trial (ChroNu study) were selected for their chronotype assessed by the Munich Chronotype questionnaire (MCTQ) and actigraphy. Total RNA was isolated from CD14 + monocytes of participants at 7 a.m. on the run-in day. Expression levels of seven clock genes ( PER1 , PER2 , PER3 , NR1D1 , NR1D2 , CRY1 and CRISPLD2 ) of individuals with early ( n = 11) or late chronotypes ( n = 19) were analysed by reverse transcription quantitative polymerase chain reaction. Difference in expression levels was tested by Mann Whitney-U test. The relative expression levels of the selected genes were not significantly different between individuals with early and late chronotypes (all p > 0.07). Contrary to expectation, clock gene expression levels at 7 a.m. was similar in individuals with early and late chronotypes. Further studies on larger sample sizes with multiple sampling time points should elucidate whether gene expression is altered at other day times underscoring the biological difference between individuals with early or late chronotypes.

Bolzano, Bernard, Vermischte Schriften 1845–1847, hg. v. Otto Neumaier, Frommann-Holzboog, Eckhart Holzboog: Stuttgart-Bad Cannstatt 2024 (Bernard Bolzano-Gesamtausgabe. Reihe I: Schriften. Bd. 20,1). - Peckhaus, Volker (zbMATH Open, Zbl. 07965480)

Maddy, Penelope, Jouko Väänänen, Philosophical Uses of Categoricity Arguments, Cambridge University Press: Cambridge 2023 (Cambridge Elements). - Peckhaus, Volker (zbMATH Open, Zbl. 1556.03003)

Computing quadratic subfields of number fields - Elsenhans, Andreas-Stephan; Klüners, Jürgen (Journal of Computational Algebra)
Given a number field, it is an important question in algorithmic number theory to determine all its subfields. If the search is restricted to abelian subfields, one can try to determine them by using class field theory. For this, it is necessary to know the ramified primes. We show that the ramified primes of the subfield can be computed efficiently. Using this information we give algorithms to determine all the quadratic and the cyclic cubic subfields of the initial field. The approach generalises to cyclic subfields of prime degree. In the case of quadratic subfields, our approach is much faster than other methods.

Konfessionskunde und Ökumene. Einleitende Einblicke und Ausblicke - Janus, Richard (Den Nächsten kennen wie sich selbst. Konfesssionkundliche Einblicke und ökumenische Ausblicke)

Den Nächsten kennen wie sich selbst. Konfessionskundliche Einblicke und ökumenische Ausblicke

Wittgenstein, Ludwig, Wiener Ausgabe, Bd. 10,3: Zettelsammlung aus den Synopsen der Manuskriptbände I bis X, hg. v. Michael Nedo, Vittorio Klostermann: Frankfurt a.M. 2024, xv, 479–726 S. - Peckhaus, Volker (zbMATH Open, Zbl. 079505172)

Shaping opportunity spaces in deep mediatization at school: principals’ strategies for dealing with unbounded digital communication - Dehmel, Lukas; Meister, Dorothee M. (International Journal of Leadership in Education)

“GET IT DIGITAL”: A SYSTEMATIC APPROACH TO DEVELOPING MULTIMEDIA OER LECTURE MATERIAL IN ELECTRICAL ENGINEERING - Bode, Henrik; Wegener, Ralf; Werle, Matthias; Siebert, Kerstin; Kiel, Martin; Temmen, Katrin (EDULEARN25 Proceedings)